Importancia de la ligadura de arteria mesentérica inferior en cirugía erradicadora de patología tumoral maligna de colon izquierdo - Vargas Lucio, Brayan José (2023)
Introduction: Proper ligation of the inferior mesenteric artery ensures en bloc excision of tumor-associated lymph nodes. Objective: To describe the reason for ligation of the inferior mesenteric artery in left hemicolectomy for colon tumor. Methodology: A narrative bibliographic review was carried out, the following databases were used: PubMed, Scielo, Springer, Nature, Elsevier, ScienceDirect, Karger and Google Scholar as a base search engine, which led to medical journals and university repositories. Results: 40 original articles, narrative and systematic bibliographic reviews and meta-analyses in English and Spanish with national and international authors dated between 2018 and 2022, in Spanish and English, were analyzed in depth. The importance in terms of ligation of the inferior mesenteric artery as it is a hemicolectomy is required to avoid hematogenous and lymphatic spread to other organs. Conclusion: Inferior mesenteric artery ligation in left hemicolectomy for colon tumor is an effective and safe strategy that minimizes hematogenous and lymphatic dissemination with a better surgical approach.